Alpha-Amylase and Endoglucanase from Bacillus amyloliquefaciens umas 1002: Gene chaacterization and expression in Escherichia coli - Muhammad Suhaib, Mat Hussin (Universiti Malaysia Sarawak (UNIMAS), 2013)
a-Amylase and endoglucanase produced by Bacillus amyloliquefaciens strain UMAS 1002, isolated from sago waste was characterized. the genes anyE and engA that encodes a-amylase and endoglucanase respectively was isolated by Polymerase Chain Reaction (PCR) and its DNA sequence was determined.